'The smoking toolkit study': a national study of smoking and smoking cessation in England - Vangeli Eleni; Stapleton John A; McEwen Andy; Jarvis Martin J; West Oliver; Shahab Lion; Fidler Jennifer A; West Robert (BMC, 2011)
Abstract Background Up-to-date data tracking of national smoking patterns and cessation-related behaviour is required to evaluate and inform tobacco control strategies. The Smoking Toolkit Study (STS) was designed for this role. This paper describes the methodology of the STS and examines as far as possible the representativeness of the samples. Methods The STS consists of monthly, cross sectional household interviews of adults aged 16 and over in England with smokers and recent ex-smokers in each monthly wave followed up by postal questionnaires three and six months later. Between November 2006 and December 2010 the baseline survey was completed by 90,568 participants. STS demographic, prevalence and cigarette consumption estimates are compared with those from the Health Survey for England (HSE) and the General Lifestyle Survey (GLF) for 2007-2009. Results Smoking prevalence estimates of all the surveys were similar from 2008 onwards (e.g 2008 STS = 22.0%, 95% C.I. = 21.4% to 22.6%, HSE = 21.7%, 95% C.I. = 20.9% to 22.6%, GLF = 20.8%, 95% C.I. = 19.7% to 21.9%), although there was heterogeneity in 2007 (chi-square = 50.30, p < 0.001). Some differences were observed across surveys within sociodemographic sub-groups, although largely in 2007. Cigarette consumption was virtually identical in all surveys and years. Conclusion There is reason to believe that the STS findings (see http://www.smokinginengland.info) are generalisable to the adult population of England.